DETERMINAN INTENSI BERWIRAUSAHA KELAS XI MPLB : SELF-EFFICACY, KREATIVITAS DAN LINGKUNGAN BELAJAR - Wulandari, Herlina Tri; Heri Susanto; Harsono; Endang Fauziati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of fostering entrepreneurial intention among vocational high school students as an effort to prepare graduates who are not only ready to work but also capable of creating business opportunities. However, entrepreneurial intention among Grade XI MPLB students has not been evenly developed, so it is necessary to examine the factors that influence it. This study aimed to analyze the effect of self-efficacy, creativity, and learning environment on entrepreneurial intention among Grade XI MPLB students at SMK Negeri 4 Klaten. This research employed a quantitative approach with an explanatory research design. The population consisted of 72 Grade XI MPLB students, all of whom were used as the sample through a saturated sampling technique. Data were collected through questionnaires using a Likert scale and then analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results showed that self-efficacy, creativity, and learning environment had a positive and significant effect on entrepreneurial intention. Creativity was the most dominant variable with a path coefficient of 0.427, followed by learning environment with 0.424, and self-efficacy with 0.285. The R-square value of 0.555 indicated that these three variables were able to explain 55.5% of the variance in entrepreneurial intention. Thus, improving entrepreneurial intention among Grade XI MPLB students can be achieved through strengthening creativity, enhancing self-confidence, and creating a conducive learning environment.